2014
DOI: 10.1155/2014/721067
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Lactic Acid Bacteria Starter Culture in the Production ofNunu, a Spontaneously Fermented Milk Product in Ghana

Abstract: Nunu, a spontaneously fermented yoghurt-like product, is produced and consumed in parts of West Africa. A total of 373 predominant lactic acid bacteria (LAB) previously isolated and identified from Nunu product were assessed in vitro for their technological properties (acidification, exopolysaccharides production, lipolysis, proteolysis and antimicrobial activities). Following the determination of technological properties, Lactobacillus fermentum 22-16, Lactobacillus plantarum 8-2, Lactobacillus helveticus 22-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 39 publications
1
52
2
1
Order By: Relevance
“…L. plantarum is well-known to be able to utilize lactose in RSM for growth. However, only some strains of L. plantarum are known to secrete proteases to utilize RSM (Akabanda et al, 2014). The L. plantarum strain used in our study was determined to be able to grow on RSM alone, without DSG (data not shown), which suggested a proteolytic ability for this strain.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…L. plantarum is well-known to be able to utilize lactose in RSM for growth. However, only some strains of L. plantarum are known to secrete proteases to utilize RSM (Akabanda et al, 2014). The L. plantarum strain used in our study was determined to be able to grow on RSM alone, without DSG (data not shown), which suggested a proteolytic ability for this strain.…”
Section: Discussionmentioning
confidence: 86%
“…A growing number of studies have shown that reconstituted skim milk (RSM) can be used as a food grade culture medium, and also as an encapsulating agent for Lactobacillus. As a culture medium, RSM needs to be supplemented with a nitrogen source which is yeast extract (Gardiner et al, 2000;Akabanda et al, 2014). Yeast extract is costly (Zarei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The content and availability of these functional components depend on the microbial diversity and the conditions of the fermentation process (Nateghi ; Akabanda et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Fermented dairy products possess diverse functional components ranging from bioactive peptides, free amino acids, organic acids and vitamins, to probiotic micro-organisms (Tamang et al 2016). The content and availability of these functional components depend on the microbial diversity and the conditions of the fermentation process (Nateghi 2012;Akabanda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Starters can use from LAB as they can convert carbohydrate into lactic acid (Nuraida, 2015). The parameter of industry to using LAB is capability to convert into lactic acid of raw materials because acidification can prevent growth of undesirable microorganisms and make the product with desirable aroma, texture, and flavor (Akabanda et al, 2014). LAB utilized milk protein, then affected to enhance free amino and peptides.…”
mentioning
confidence: 99%